Influence of Nano- and Microplastic Particles on the Transport and Deposition Behaviors of Bacteria in Quartz Sand - He, L.; D. Wu; Rong, H.; M. Li; Tong, M.; Kim, H. (Environmental Science and Technology, 2018)
Plastic particles are widely present in the natural environment and are highly likely to interact with bacteria (the ubiquitous microbes in the natural environment), which might affect the transport and deposition of bacteria in porous media. In this study, the significance of plastic particles from nanoscale to micrometer-scale (0.02-2 μm) on the transport and deposition behaviors of bacteria (Escherichia coli) in quartz sand was examined under environmentally relevant conditions in both NaCl and CaCl2 solutions at pH 6. The results showed that the presence of different-sized plastic particles did not affect bacterial transport behaviors at low ionic strength (10 mM NaCl and 1 mM CaCl2), whereas, at high ionic strength conditions (50 mM NaCl and 5 mM in CaCl2), plastic particles increased bacterial transport in quartz sand. At low ionic strength conditions, the mobility of both plastic particles and bacteria was high, which might drive the negligible effects of plastic particles on bacterial transport behaviors. The mechanisms driving the enhanced cell transport at high ionic strength were different for different-sized plastic particles. Specifically, for 0.02 μm nanoplastic particles, the adsorption of plastic particles onto cell surfaces and the repel effect induced by suspended plastic particles contributed to the increased cell transport. As for 0.2 μm microplastics (MPs), the suspended plastic particles induced repel effect contributed to the increased cell transport, whereas, for 2 μm MPs, the competition deposition sites by the plastic particles were the contributor to the increased cell transport. © 2018 American Chemical Society.
Keywords: article; Bacteria; Bacteria (microorganisms); Bacterial transport; bacterium; calcium chloride; Cell membranes; Cytology; Deposition; Deposition behavior; Escherichia coli; High ionic strength; ionic composition; Ionic strength; Low ionic strength; Micrometer scale; Microplastic; Microplastic particles; nanoparticle; nanoplastic; Natural environments; Particle size; pH measurement; plastic; Plastic particle; Plastics; pollutant transport; porosity; Porous materials; Quartz; Sand; silicon dioxide; Sodium chloride; unclassified drug